2009
DOI: 10.1002/lsm.20874
|View full text |Cite
|
Sign up to set email alerts
|

A high‐throughput model for fat graft assessment

Abstract: This model of fat-grafting and early apoptosis can be used to screen agents and grafting methods and predict long-term graft survival. We show that levels of apoptosis within ten days correlate with weight, DNA, and histology, at six weeks. Using this model, long-term adipocyte survival and graft take can be predicted during the first 10 days post-implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…This team from the Massachusetts General Hospital showed that grafts treated with P188 exhibited a 50 percent decrease in apoptosis compared to the saline-treated controls and achieved a remarkable 72 percent weight-based survival after 6 weeks. These results are confirmed by another study ( 80 ), assessing DNA contents using PicoGreen analyses, which showed higher fat survivability with P188. These findings led to the development of fat-processing systems (Vitality, SIENTRA, Irvine, CA, USA), with ongoing multicenter studies to clinically confirm these excellent results.…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...supporting
confidence: 76%
“…This team from the Massachusetts General Hospital showed that grafts treated with P188 exhibited a 50 percent decrease in apoptosis compared to the saline-treated controls and achieved a remarkable 72 percent weight-based survival after 6 weeks. These results are confirmed by another study ( 80 ), assessing DNA contents using PicoGreen analyses, which showed higher fat survivability with P188. These findings led to the development of fat-processing systems (Vitality, SIENTRA, Irvine, CA, USA), with ongoing multicenter studies to clinically confirm these excellent results.…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...supporting
confidence: 76%
“…No changes are seen across all other endpoints measured during this initial 24-hour period. 9 When grafts were analyzed at 6 weeks for metabolic activity, P188-treated grafts demonstrated almost 3-fold higher activity levels (Figs. 4 and 5).…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent graft loss results from removal of dead cellular debris following revascularization. 9 Thus far, efforts to blunt the initial ischemic insult and protect cells until sufficient vascularity can be established have led to modest results.…”
mentioning
confidence: 99%
See 1 more Smart Citation